Верховенство права как принцип интеграции правовых систем в современном мире - Скакун, Ольга Федоровна; Скакун, Ольга Федорівна; Skakun, Ol'ga (My University, 2009)
Integration of t h e legal s y s t e m of Ukraine in E u r o p e a n legal space on the basis of principle of s u p r e m a c y of right requires its reformation, perfection of all types of normative and law applying processes, legal practice on the real providing of rights and freedoms of citizens. And it is possible only at the high-quality increase of level of legal culture of office w o r k e r s , j u d g e s , w o r k e r s of law e n f o r c e m e n t a u t h o r i t i e s , skilled t r a i n i n g of personnels, growth of authority of s t a t e power.
Скакун О. Ф. Верховенство права как принцип интеграции правовых систем в современном мире / О. Ф. Скакун // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 35-44.
Keywords: верховенство права; интеграция; правовые системы современности; інтеграція; правові системи сучасності; the rule of law; integration; legal systems of the